Association of adiponectin protein and ADIPOQ gene variants with lumbar disc degeneration - KHABOUR, OMAR F. (D.A. Spandidos, 2014)
Lumbar disc degeneration (LDD) is a widespread public health problem that may lead to disability and loss of productivity. Adiponectin is an adipokine secreted by adipose tissue and has been shown to be involved in cartilage homeostasis. In the present study, the association between the rs266729 (−11377C/G) and rs2241766 (45T/G) single nucleotide polymorphisms (SNPs) in the adiponectin gene (ADIPOQ) and LDD was investigated. In addition, the correlation between the plasma adiponectin level and LDD was examined. A total of 289 subjects, 168 patients with LDD and 122 healthy individuals, were recruited in the study. All subjects were genotyped for rs266729 and rs2241766 SNPs using polymerase chain reaction-restriction fragment length polymorphism. Circulating levels of adiponectin protein were measured using the ELISA technique. A strong association was found between adiponectin level and LDD (P<0.01), where high levels of adiponectin were found in patients compared with healthy controls. The increase in adiponectin level was not affected by gender. However, no significant differences were found in the genotype distribution or allelic frequency of the two examined polymorphisms between patients with LDD and healthy controls (P>0.05). In conclusion, adiponectin appears to be elevated in patients with LDD. The rs266729 and rs2241766 SNPs in the ADIPOQ gene are not associated with LDD.